Influence of Menstrual Cycle or Hormonal Contraceptive Phase on Physiological Variables Monitored During Treadmill Testing - Taipale-Mikkonen, Ritva S.; Raitanen, Anna; Hackney, Anthony C.; Solli, Guro Strøm; Valtonen, Maarit; Peltonen, Heikki; McGawley, Kerry; Kyröläinen, Heikki; Ihalainen, Johanna K. (Frontiers in Physiology, 2021)
Purpose To examine the influence of menstrual cycle (MC) and hormonal contraceptive (HC) cycle phases on physiological variables monitored during incremental treadmill testing in physically active women (eumenorrheic, EUM=16 and monophasic HC-users, CHC=12). Methods Four running tests to exhaustion were performed at bleeding, mid follicular (mid FOL) / active 1, ovulation / active 2, and mid luteal (mid LUT) / inactive. HC and MC phases were confirmed from serum hormones. Heart rate (HR), blood lactate (Bla), and V̇O2 were monitored, while aerobic (AerT) and anaerobic (AnaT) thresholds were determined. V̇O2peak, maximal running speed (RUNpeak), and total running time (RUNtotal) were recorded. Results No significant changes were observed in V̇O2 or Bla at AerT or AnaT across phases in either group. At maximal effort, absolute and relative V̇O2peak, RUNpeak, and RUNtotal remained stable across phases in both groups. No significant fluctuations in HRmax were observed across phases, but HR at both AerT and AnaT tended to be higher in CHC than in EUM across phases. Conclusions Hormonal fluctuations over the MC and HC do not systematically influence physiological variables monitored during incremental treadmill testing. Between group differences in HR at AerT and AnaT underline why HR-based training should be prescribed individually, while recording of MC or HC use when testing should be encouraged as phase may explain minor, but possibly meaningful, changes in e.g. Bla concentrations or differences in HR response.